(untitled) (Communications in Mathematical Research, 2021)
Let X be a Minkowski plane, i.e., a real two dimensional normed linear space. We use projections to give a definition of the angle A_q(x, y) between two vectors x and y in X, such that x is Birkhoff orthogonal to y if and only if A_q(x, y) = π2. Some other properties of this angle are also discussed.